AN ANALYSIS OF THE HADICAL STORY OF PROPHET IBRAHIM AND SARAH WITH A ZHOLIM KING AS A TEACHING MATERIAL IN ISLAMIC EDUCATION - Salmah Salmah (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2017)
In the world of education, a delivery of stories is one of the effective strategies to deliver educational materials to children or learners. As the matter of facts, sometimes the stories told to the children or learners are taken from untruthful sources or fairy tales that will cause a delusion in the child's mind. It is important for parents or educators to convey valued stories coming from the teachings of Islamic values, such as the stories of the previous people delivered by the Prophet Mohammad through his traditions. The purpose of this study is to examine the editorial accounts of the story of the prophet Abraham and Sarah with the zholim King, and to know the understanding of the hadith and the educational analysis associated with this hadith. To obtain the information on the hadith about the story, the researcher uses a takhrîj hadith method, in as much as, it was found there are various relevant hadiths of the Prophet Muhammad related to the story. These hadiths have been analyzed for their historical qualities and linked them with Islamic education materials.